G70(P) Nitrous oxide abuse resulting in sub-acute degeneration of the spinal cord – a case report. (25th October 2020) - Horner, RL; Shields, A; Ramiah, R
Abstract : A case report of a 15 year old boy presenting with a 3 week history of progressive ataxia and sensory loss. Examination revealed complete bilateral sensory loss from toes to mid-thigh and sensory loss in both little fingers. He admitted to heavy inhalational abuse of nitrous oxide and daily use of cannabis. No other medical problems and no family history of note. Blood tests revealed a normal total vitamin B12 level (247 ng/L), but raised methylmalonic acid (500 nmol/L) and reduced active vitamin B12 (30 pmol/L), this was indicative of an active vitamin B12 deficiency. An MRI demonstrated high signal changes in the posterior cord extending from C1 to the lower thoracic cord which was typical of sub-acute degeneration of the spinal cord. Vitamin B12 deficiency is known to cause sub-acute combined degeneration of the spinal cord. He was treated with daily vitamin B12 injections and showed some clinical recovery whilst an inpatient. Conclusion: Regular nitrous oxide abuse causes an active vitamin B12 deficiency; usually total vitamin B12 is normal and more sensitive markers including homocysteine, methylmalonic acid (MMA) and active vitamin B12 are needed for diagnosis. Nitrous oxide abuse is commonplace amongst teenagers and young adults, it is important that paediatricians are made aware of how commonly it is abused and the neurological consequences. Nitrous oxide is cheap and easy to obtain; particularly as it can be bought legally for whipping cream. Those abusing it regard nitrous oxide to be a safe legal high and a thorough drug history is needed to recognise abuse, consideration should also be made for patients requiring recurrent nitrous oxide for medical procedures and pain relief.